Aerodynamic behaviour of single sport jersey fabrics with different roughness and cover factors - Oggiano, L.; Troynikov, O.; Subic, A.; Alam, F. (Sports Engineering, 2009)
Wind tunnel testing has been carried out on nine-knitted single jersey fabrics (100% polyester) using cylinder and leg models to determine its aerodynamic behaviour over a range of speeds (20-80 km/h) representative of sports activities. Strong correlation between fabric manufacturing (cover factor) and fabric roughness and aerodynamic parameters has been established. Similar aerodynamic behaviour of fabrics was observed when tested on the cylinder model and on the leg model.